The Psychometric Properties of the Norwegian version of he Child and Adolescent Trauma Screen (CATS Caregiver) - Borren, Ingrid; Bania, Elisabeth Valmyr (PsykTestBarn, 2022)
Description: The Child and Adolescent Trauma Screen (CATS Caregiver, named KATES Omsorgsgiver in Norwegian) is a screening instrument providing preliminary prognostic information about posttraumatic stress in children and adolescents aged 3 to 17 years. CATS Caregiver is available in two age-adjusted versions with similar construction for caregivers of 3- to 6-year-olds and for parents/caregivers of 7- to 17-year-olds. CATS Caregiver consists of two parts: part 1 maps experiences with traumatic events, and part 2 measures symptoms of posttraumatic stress. The four symptom categories in part 2 were developed to match the diagnostic changes of the DSM-5 trauma diagnosis. Sachser et al. (2017) developed and validated CATS Caregiver, and researchers from The Norwegian Centre for Violence and Traumatic Stress Studies (NKVTS) were involved in this work and responsible for translation to Norwegian. Literature search: The literature search resulted in one published article including a Norwegian sample reporting psychometric information for the caregiver version of CATS. Psychometrics. Sufficient/good internal consistency was indicated for the four subscales of the screening instrument for parents/caregivers of 7- to 17-year-olds. The underlying DSM-5 factor structure for posttraumatic stress disorder was confirmed by confirmatory factor analysis in a sample of parents/caregivers from Norway, Germany, and the US. The results also indicate evidence for convergent and construct validity (this was not tested for the caregiver version for3- to 6-year-olds). A test–retest score in the relevant study does not exist; neither does a measure for sensitivity to change, nor Norwegian norms. Conclusion: The documentation is not sufficient to firmly conclude on the psychometric properties of CATS Caregiver for children/adolescents aged 7 to 17 years. There is a need for more studies from Scandinavian populations, particularly test–retest scores and norm data. Documentation is also needed for the parent version of the scale for 3- to 6-year-olds. Hence, the scale must be used with caution in Norway for all age groups.